A federated interoperability architecture for health information systems. (1st January 2013) - Ciampi, Mario; De Pietro, Giuseppe; Esposito, Christian; Sicuranza, Mario; Donzelli, Paolo
He last decade has been characterised by the proliferation of several projects for integrating the already-existing health information systems so as to form national or transnational infrastructures for sharing medical data. This evolution is felt as a promising solution for improving the provided healthcare and reducing its costs by avoiding unnecessary examinations. However, such a vision comes with several challenging issues, in terms of interoperability and security. This paper presents an architecture for federating health information systems in a secure manner, and its concrete implementation. The quality of this implementation is assessed by means of several experiments for measuring the time needed for the retrieval and notification of documents.